The power of voice in transforming multilingual societies - Erling, Elizabeth J.; Heiling, Angelika; Korb, Christina; Gspandl, Julia 1994- (Critical language and literacy studies, 2023)
"Drawing upon the framework of linguistic citizenship, the chapters in this book link questions of language to sociopolitical discourses of justice, rights and equity, as well as to issues of power and access. They present powerful evidence of how marginalized speakers reclaim their voices and challenge power relations"--